Deagglomeration of High Purity Fine Alumina Powder via pH Control - Muchtar, Andanastuti; Wati, Norazmira; Jaafar, Nor Azri (ASEAN Journal of Chemical Engineering, 2002)
This paper presents results from a study on the effect of the pH of suspensions on the deagglomeration of a high-purity (99.99%), fine-grained alumina powder. The pH of the suspension was varied between pH 2 and 3. It is the aim of the study to determine the best pH for a successful dispersion of the alumina powders in the suspension. A series of rheological studies and analytical work under Scanning Electron Microscopy were conducted. It was found that the best pH was pH 2. Data obtained from rheological studies using a viscometer showed that the alumina suspension prepared at pH 2 was least viscous, which may be taken as a negative indicator of the presence of agglomerates. This hypothesis is validated by visual inspection using SEM. For the pH 2 samples, a successful removal of the agglomerates in the green compact has encouraged the sinterability of the samples and thus, resulted in an earlier sintering process at a low-firing temperature. In addition, the sintering characteristics and microstructures of the samples prepared with a pH 2 suspension are also presented.